A Comparative Study of Social Media Addiction Among Turkish and Korean University Students - Aylin Tutgun Ünal (Journal of Economy Culture and Society)
Social networks, where access is provided through mobile phones via the internet, have transformed our communication habits, while also paving the way for social media addiction. As social media addiction harms all areas of a person’s life, this research has focused on identifying the addictions of young people who have not started their professional life yet. Considering that technology is involved in people’s lives to different extents in different countries, country comparisons are considered important in digital addiction research. This study aims to compare social media addiction among university students from South Korea and Turkey. The “Social Media Addiction Scale” developed by Tutgun-Ünal and Deniz (2015) was used in this study conducted with 270 university students. Some of the findings obtained in studies using a comparative survey model are as follows: (a) social media addiction is low in both countries, (b) South Korean students’ addiction was found at a higher level than those from Turkey, (c) students in South Korea are getting more emotional support from social media, (d) the addiction of South Korean students on conflict dimension was found higher, (e) students in Turkey communicate with their families via social media more than those in South Korea.